2003
DOI: 10.1017/s0952836903004060
|View full text |Cite
|
Sign up to set email alerts
|

An updated description of the New Guinea singing dog (Canis hallstromi, Troughton 1957)

Abstract: In 1957, Troughton described the wild dog of New Guinea, naming it Canis hallstromi. Here the description given by Troughton is expanded by the addition of morphological, molecular and behavioural information collected from both captive and wild New Guinea singing dogs subsequent to the original description. The data support Troughton's identification of this canid as a unique taxon, although further studies are needed to clarify the exact level of taxonomic differentiation of this rare and possibly highly end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…The New Guinea singing dog samples were collected from among a hundred or so animals presently in the United States. The worldwide population, outside of Papua New Guinea, is only about 300 dogs derived from eight wild‐caught animals, while the US population originated from four founders brought into the United States in 1957, 1987 and 1994 (http://www.canineworld.com/ngsdcs/history.html) (8). Even though sampling numbers were comparatively low, it is noteworthy that alleles found in the New Guinea singing dog were also found in the Australian dingo.…”
Section: Discussionmentioning
confidence: 99%
“…The New Guinea singing dog samples were collected from among a hundred or so animals presently in the United States. The worldwide population, outside of Papua New Guinea, is only about 300 dogs derived from eight wild‐caught animals, while the US population originated from four founders brought into the United States in 1957, 1987 and 1994 (http://www.canineworld.com/ngsdcs/history.html) (8). Even though sampling numbers were comparatively low, it is noteworthy that alleles found in the New Guinea singing dog were also found in the Australian dingo.…”
Section: Discussionmentioning
confidence: 99%
“…Although the recent papers of Koler-Matznick (2003, 2007 and Crowther et al (2014) do not explicitly state the species concept followed, both studies have a strong emphasis on the differentiation of each lineage from other dogs and wolves, and on their history of genetic isolation of Dingo and New Guinea Singing Dog from each other and from other canids since their arrival in Australia and New Guinea, respectively. Both also downplay the evidence of hybridization between these 'native' dog populations and more recently introduced dog breeds, on the grounds that interspecific hybridization is common among canids and represents a shared primitive characteristic.…”
Section: Matters Of Principle-species and Domesticatesmentioning
confidence: 99%
“…2003). Further, studies of mtDNA and the Major Histocompatibility Complex have shown extensive haplotype sharing between these two populations (Oskarsson et al .…”
Section: Introductionmentioning
confidence: 99%